Ocular Melanoma Presenting as Masquerade Syndrome - Macedo, Sara Simões (Eur J Case Rep Intern Med, 2019)
A masquerade syndrome is an ophthalmological entity where a neoplasm mimics an inflammatory condition. Ocular melanoma (chiefly uveal) may present with symptoms suggestive of intraocular inflammation such as endogenous endophthalmitis. Ocular melanoma is most commonly found in middle-aged and older caucasian patients. One-third of all uveal melanoma cases present asymptomatically. Early diagnosis facilitates treatment before ocular melanoma reaches metastatic stage IV. Current therapy options for stage IV patients are palliative care and clinical trial participation. LEARNING POINTS: Masquerade syndrome and intraocular haemorrhage can hide a neoplastic aetiology. A biopsy should be carried out for correct diagnosis if intraocular haemorrhage is present and a neoplastic pathology is suspected. A multidisciplinary approach should be adopted to enhance the quality of life of patients with metastatic ocular melanoma.